Pengaruh Green Accounting, Kinerja Lingkungan, dan Corporate Social Responsibility terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Ningrum, Safita; Gunarianto, Gunarianto; Hasan, Khojanah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research aims to examine green accounting, environmental performance and corporate social responsibility on profitability in manufacturing companies listed on the IDX in 2019-2021. This research uses a quantitative approach using secondary data with the sample used being 23 companies with a 3 year time period whose data processing was carried out using the IBM application. SPSS 25. The research results show that partially green accounting has a negative effect on company profitability with a sig value of 0.039<0.05. Meanwhile, environmental performance has no influence on profitability because the sig value is 0.133>0.05. And corporate social responsibility has a positive effect on profitability with a sig value of 0.009 <0.05. And the results of research simultaneously green accounting, environmental performance, and corporate social responsibility have a significant influence on company profitability with F test calculation results of 0.012<0.05.